The Impacts of Road Pricing on Businesses - Mahendra, Anjali (IOS Press, 2013)
Road pricing is the name given to a variety of systems which charge road users a fee to mitigate the social costs of using their vehicles. The charges can be introduced to alleviate the costs of delays caused by congestion, environmental problems and the health costs resulting from pollution and accidents. But although the idea of road pricing has been around for many decades, it can prove difficult to implement due to a variety of social and political concerns. This book focuses on the institutional challenges to the implementation of road pricing policies by examining two cases: the potential impacts of road pricing on businesses and freight transport in the Netherlands and the implications of the London (UK) congestion charge for companies in key economic sectors. Distance-based road pricing has been the subject of a heated political debate in the Netherlands, and the study discusses the use of different theoretical frameworks to understand how its introduction might affect commercial decisions and relationships. This conceptual framework is adapted and applied in the second part of the book to conduct a survey of businesses in a number of economic sectors in London, and is especially of interest to other cities considering the introduction of road pricing in the future. Using institutional analysis, a paradigm not often employed before in studies of road pricing, this book seeks practical and theoretical answers to the subject, and will be of value and interest to all those involved in addressing the growing problems of road traffic congestion worldwide.